The Effectiveness of Various Physical Activities on Glycemic Control in Individuals with Prediabetes Mellitus in Semarang Municipality - Arwani, Arwani; Widiyanto, Budi; Widiyati, Sri (Universitas Muhammadiyah Semarang, 2023)
Currently, diabetes mellitus is a prevalence in Indonesia, with a rate of 2.1% based on relevant diagnoses or symptoms. It is estimated that by 2030, the number of individuals suffering form diabetes mellitus will reach 21.3 million. Conversely, the proportion of individuals with prediabetes is 2-4 times higher than those with diabetes. Physical activity has been identified as a preventive measure for prediabetes. Several studies have demonstrated the significant impact of physical activity on glycemic control. This study aimed to determine the effectiveness of different physical activities on glycemic control in prediabetic clients residing in Semarang municipality. A randomized control trials with a pretest-posttest design was conducted on 60 prediabetic clients using different treatments, including healthy/slow walking, brisk walking, and a combination of both slow and brisk walking. The data of the study were analyzed using univariate, and bivariate analysis using repeated ANOVA. All statistical analyses were carried out using SPSS version 22. The average level of glycemic control before intervention in the healthy walking group was 5.57%, which decreased to 5.46% after intervention. The combination group decreased from 5.93% to 5.78%, and the slowly walking group decreased from 5.74% to 5.71%. However, there was no significant effect of slowly walking on glycemic control (HbA1c levels). In contrast, brisk walking and the combination of slow walking and brisk walking had a significant effect on glycemic control (p<0.05). The combination of the physical activity group demonstrated the greatest impact on glycemic control (p<0.05).